A pilot study on interprofessional education: how prepared are faculty to teach?. Issue 4 (8th August 2019) - Christianson, Tracy M.; Bainbridge, Lesley; Halupa, Colleen
ABSTRACT: Faculty development for interprofessional (IP) teaching and learning is a complex and evolving part of educators' preparation for IP teaching and learning. A review of the literature highlighted a gap of rigorous research in the area of faculty development for interprofessional education (IPE). This pilot study used a mixed-methods approach to explore how faculty development affected educators' preparedness for IP teaching and looked at the possible effects of IP and teaching experiences. Pre- and post-faculty development evaluations were captured using validated instruments and helped to explore the impact faculty development had on educators' preparedness for IPE. The qualitative data offered insights using participants' perspectives about IPE where the quantitative method could not. This pilot study offers findings that explored important characteristics that may have a role in faculty preparation for IPE teach and learning and could possibly be used in future research.